Lanthanum-based perovskites obtained by the polymeric precursor method - Melo, Danniely S.; Marinho, Erika P.; Soledade, Luiz E. B.; Melo, Dulce Maria A.; Lima, Severino Jackson G.; Longo, Elson [UNESP]; Santos, Ieda Maria Garcia; Souza, Antonio G. (Springer, 2008)
Cobalt oxides, specially the ones with perovskite structure, are of a high technological interest, due to their interesting optical, electrical and magnetic properties. La(1 -x)Ca(x)CoO(3) powder samples were synthesized by the polymeric precursor method, with x varying from 0 to 0.4. The powder precursors were characterized by TG/DTA, XRD and IR. The TG curves showed several thermal decomposition steps; the first one is ascribed to the loss of water and the remaining steps are related to the combustion of the organic matter. The XRD patterns indicated only the presence of the perovskite phase. Moreover, the structure changes from rhombohedral to cubic, as calcium is added to the perovskite and the calcination temperature increases.